Neutrophil-to-lymphocyte Ratio: A Surrogate Marker for Prognosis of Oral Squamous Cell Carcinoma - Mahalakshmi, R; Boaz, Karen; Srikant, N; Baliga, Mohan; Shetty, Premalatha; Prasad, Mukul; Yellapurkar, Shweta; Lewis, Amitha J (Indian Journal of Medical and Paediatric Oncology, 2018)
Context: Recent studies show that enzymatic contents of the neutrophil granules have a remarkable ability to modulate the tumor microenvironment by causing apoptosis of T-lymphocytes which leaves the host's cell-mediated immunity at stake. The preoperative neutrophil to lymphocyte ratio (NLR) is considered to be an indicator of the immune status of the patients with oral squamous cell carcinoma (OSCC), which will thereby help in predicting the course of the disease. Aims: The aim is to assess the NLR and histopathological prognostic factors pertinent to infiltration of the surrounding structures and correlate them with the clinical prognostic outcomes of OSCC. Settings and Design: This retrospective study involved the retrieval of formalin-fixed, paraffin-embedded, hematoxylin, and eosin-stained sections of 55 cases of OSCC from the departmental archives from 2006 to 2014. Subjects and Methods: Grading of each case was done by Bryne's grading system. The preoperative complete blood counts, relevant case history, and clinical data of the patients involved in the study were collected from the institutional medical records. The NLR was calculated by dividing the serum neutrophil count by the serum lymphocyte count. Statistical Analysis Used: The median NLR was compared between the controls and OSCC cases using Wilcoxon-signed rank test, and the Kaplan-Meier survival analysis was carried out to predict the survival and recurrence status of OSCC. Results: Higher NLR was seen in lymph node and margin-involved cases and also in patients who had tumor recurrence. Kaplan-Meier survival analysis showed that the mean survival dropped from 26 to 4.5 months when NLR ≥5 (P = 0.052). Conclusion: Neutrophil-to-lymphocyte ratio can be used as a prognosticator of survival, recurrence, lymph node status, and margin status in OSCC.
Keywords: Cannibalism; interleukin-8; neutrophil; neutrophil to lymphocyte ratio; oral squamous cell carcinoma; prognosis